Dye removal by thin film composite (TFC) membrane produced through interfacial polymerization technique - Daeng Mohd Ashik, Bachok (2012)
There are many types of dye removal technique such as biological method, chemical method,and physical method. Membrane - filtration is one of the physical methods that widely use for dye removal.Thin film composite membranes were synthesized through interfacial polymerization at fix monomer concentration of 2% w/v at different reaction time. The reaction between triethanolamine (TEOA) aqueous and trimesoylchloride (TMC) in hexane produce new layer polyester on top of polyethersulfone (PES) miroporous support.The fabricated thin film composite membranes were characterized in term of flux and permeability.In addition, the membrane performances were tested for dye removal using methylene blue as dye model.Increasing the reaction time resulted in decreasing the water permeabilities and improving removal efficiency.